Study protocol: post-harvest losses of fruits and vegetables and their relationship with the nutritional status of women and children - Twum-Dei, Benedicta; Lutterodt, Herman Erick; Annan, Reginald Adjetey; Aduku, Linda Nana Esi (Frontiers in Public Health, 2025)
IntroductionSub-Saharan Africa loses up to 50% of fruits and vegetables produced annually, with Ghana alone reporting post-harvest losses ranging between 30 and 50% across the value chain. These losses significantly threaten nutrition security by reducing the availability of essential nutrients in the food system. Capturing these lost nutrients is crucial to promoting healthy and affordable diets. This study protocol presents a community-based randomised controlled trial (RCT) being implemented in the Ho West District of Ghana. The trial aims to investigate the association between post-harvest loss (PHL) of fruits and vegetables and the nutritional status of women and children, while also identifying loss drivers across the value chain.MethodsThis experimental trial study employs an untreated control group design and involves 280 participants, comprising 70 farmers, 70 traders, and 140 women and their children. Socio-demographic data and post-harvest practices will be collected from all participants to estimate nutritional losses. Dietary intake of fruits and vegetables will be assessed using food frequency questionnaires, while food consumption and household hunger will be measured using validated scoring tools. Anthropometric and nutritional measurements will be recorded for women and children using WHO protocols. Women in the intervention arm will receive nutrition education and counselling focused on storage and preservation strategies to reduce food waste.Potential impactThis study will provide evidence on the link between post-harvest loss and nutritional outcomes and inform practical interventions for reducing PHL at the community level. It offers a platform for building capacity among farmers, traders, and caregivers through increased awareness and behaviour change. By integrating nutrition education into PHL mitigation, the findings have the potential to influence food systems policy, improve household nutrition, and contribute to global efforts to reduce food loss. The trial is currently ongoing, and this protocol outlines the study’s design, methodology, and implementation framework.Clinical trial registrationThis trial is registered with the Pan African Clinical Trial Registry (PACTR202310582275172).